Nursing of a patient with oculomotor nerve paralysis treated with plum-blossom needle tapping therapy (梅花针叩刺法治疗1例动眼神经麻痹患者的护理体会) - LI Jinhuan (李金环); YIN Kexin (尹可欣); YANG Tingting (杨婷婷); CHEN Xiangping (陈香平); LIU Hongyan (刘红艳); JIA Zongcan (贾宗灿) (Association of Integrative Nursing, 2024)
Oculomotor nerve palsy is a nerve condition that affects patient's vision and quality of life. This article summarizes the nursing experience of a patient with mild oculomotor nerve paralysis treated with plum-blossom needle tapping therapy. Based on the differentiation of symptoms and signs in Traditional Chinese Medicine, plum-blossom needle technique therapy, as well as daily life support, dietary care, medication, and emotional nursing interventions, can effectively improve symptoms such as ptosis, strabismus, and limited eye movement in the patient. (动眼神经麻痹严重影响患者视觉及生活质量。本文总结采用梅花针叩刺法治疗1例轻度动眼神经麻痹患者的护理经验。根据护理评估及中医辨证分型, 在生活起居、饮食护理、情志护理基础上, 采用梅花针中医护理技术, 有效改善了患者上睑下垂、斜视、眼球活动受限等症状。)